2007
DOI: 10.1097/01.mao.0000281802.59444.02
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Follow-Up of a Consecutive Series of Children With Multichannel Cochlear Implants

Abstract: This long-term report shows that many profoundly hearing-impaired children using cochlear implants can develop functional levels of speech perception and production, attain age-appropriate oral language, develop competency level in a language other than their primary language, and achieve satisfactory academic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
86
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 30 publications
11
86
0
5
Order By: Relevance
“…The remaining group comprised four college students, three university students, three actively employed and one (stay-at-home) parent. Another study on speech and language achievements, academic and occupational status of adolescents and young adults using CI for more than 10 years [12] found similar results and concluded, that the young people show satisfactory academic performance. As in [11] information on professional education and career progression was not available.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The remaining group comprised four college students, three university students, three actively employed and one (stay-at-home) parent. Another study on speech and language achievements, academic and occupational status of adolescents and young adults using CI for more than 10 years [12] found similar results and concluded, that the young people show satisfactory academic performance. As in [11] information on professional education and career progression was not available.…”
supporting
confidence: 76%
“…As in [11] information on professional education and career progression was not available. The studies [9][10][11][12] are retrospective and do not include control groups.…”
mentioning
confidence: 99%
“…Uziel et al [31] also reported 10-year speech intelligibility outcomes (SIR), communication mode and academic/occupational status of 79 unilaterally implanted children (implanted between 1.9 and 14 years of age). After 10 years of implant experience, 40% of the children developed speech intelligible to the average listener (SIR 5) and 27% developed speech intelligible to a listener with some experience of deaf person's speech (SIR 4).…”
Section: Discussionmentioning
confidence: 92%
“…However, our bilaterally implanted children obtained comparable results after only 4-11 years of unilateral and 3 years of bilateral implant use. Moreover, most of our bilaterally implanted children were congenitally deaf while most of the unilaterally implanted children in the Beadle et al [30] and Uziel et al [31] study were postlingually deaf.…”
Section: Discussionmentioning
confidence: 93%
“…The recipient's knowledge and understanding of CIs, their communication needs and skills, psychological strengths and weaknesses, attitude towards implantation and availability of a support network is also assessed before implantation (Paul & Whitelaw). A team of allied and medical professionals are involved throughout the implantation and (re)habilitation of CI recipients (Paul & Whitelaw. It is important to note that CIs also do not restore hearing to that of a hearing person and may not be an ideal solution for everyone, with research indicating some people, in fact, turn off their cochlear implant and do not use them (Paul & Whitelaw;Rose, Vernon, & Pool, 1996;Uziel et al, 2007) The cost of a CI varies from country to country and between devices. To give an idea of the cost of a CI device, in 2005 the cost of a Nucleus® Freedom™ CI system was $25,070AUD (Access Economics, 2006).…”
Section: Cochlear Implantsmentioning
confidence: 99%